MANAGEMENT OF MANGROVE ECOSYSTEM POTENCY IN KUALA LANGSA, ACEH - Nabil Zurba; Hefni Effendi; . Yonvitner (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
The potency of mangrove ecosystems can be a provider of economic resources, preserving the ecological environment and providing environmental services. The existence of mangroves in Kuala Langsa is important to study about the economic potential, the potential of carbon sequestration in the form of biomass, coastal tourism potential and social potential of society in support of its development efforts. The result of the research shows that the potential existence of mangrove ecosystem to fishery sector is Rp. 657.563.000 / year, carbon sequestration potential in the form of biomass of 180.365 ton /year, with the economic value of carbon trade of Rp. 2.344.745.000/year, economic potential of coastal tourism reached Rp 22,921,107,253/year. Overall, the estimated total potential of existing mangrove ecosystems in Kuala Langsa is Rp. 29.923.415.253/year. To manage these potentials, a conservation strategy is required, performance improvement of customary institutions and the existence of such management institutions must be continuously strengthened. Keywords: institutional, Kuala Langsa, mangrove, potency, strategic management